Fluid balance during training in elite young athletes of different sports - Arnaoutis, G.; Kavouras, S. A.; Angelopoulou, A.; Skoulariki, C.; Bismpikou, S.; Mourtakos, S.; Sidossis, L. S. (The Journal of Strength and Conditioning Research, 2015)
Although there are many studies demonstrating a high percentage of adult athletes who start exercise in suboptimal hydration state, limited data concerning hydration levels in athletic youth exist. The purpose of this study was to identify the hydration status of elite young athletes of different sports, during a typical day of training. Fifty-nine young elite male athletes from different sports (basketball, gymnastics, swimming, running, and canoeing) participated in the study (age: 15.2 ± 1.3 years; years of training: 7.7 ± 2.0). Hydration status was assessed in the morning, before and immediately after practice. Data collection took place at the same time of the day, with mean environmental temperature and humidity at the time of the measurements at 27.6 ± 0.9° C and 58 ± 8%, respectively. All athletes trained for approximately 90 minutes, and they were consuming fluids ad libitum throughout their practice. Over 89% of the athletes were hypohydrated (urine specific gravity [USG] =1.020 mg/dl) based on their first morning urine sample. Pretraining urine samples revealed that 76.3% of the athletes were hypohydrated, whereas a significant high percent remained hypohydrated even after training according to USG values =1.020 mg·dl-1 (74.5%) and urine color scale: 5-6 (76.3%). Mean body weight loss during training was -1.1 ± 0.07%. We concluded that the prevalence of hypohydration among elite young athletes is very high, as indicated by the USG and urine color values. The majority of the athletes was hypohydrated throughout the day and dehydrated even more during practice despite fluid availability.